The Transition from Conventional Constitutions to Digital Law: Constitutional Law Challenges in the Age of Artificial Intelligence - Septia, Sya’baniatie Ninda (Journal of International Multidisciplinary Research, 2026)
The rapid advancement of digital technology and artificial intelligence (AI) in the twenty-first century has fundamentally transformed the structure of modern constitutional governance. Digitalization has reshaped the interactions between governments and citizens, altered the patterns of political participation, and presented major challenges to constitutional principles. This study aims to analyze the implications of technological development for constitutional law and propose the concept of a digital constitution as an adaptive framework in the AI era. This study employs a normative legal method, using both conceptual and statutory approaches. Legal materials consist of primary, secondary, and tertiary sources, which are analyzed qualitatively and descriptively. The findings reveal that, while digital transformation enhances governmental efficiency and public transparency, it also generates serious risks, including data misuse, digital surveillance, and political disinformation. These dynamics demand a reinterpretation of constitutional norms to protect citizens' digital rights in cyberspace. The concept of a digital constitution is proposed as a normative response that integrates digital rights into constitutional rights and reaffirms the principle of the rule of law within technological governance. To achieve a democratic and just constitutional order, it is crucial to strengthen regulatory frameworks, ensure algorithmic accountability, and foster collaboration among state institutions, civil society, and the private sector. Ultimately, constitutional law must evolve into an adaptive, transparent, and fair system that can address the profound challenges of the digital and AI-driven era.